The discovery of a massive supercluster at z=0.9 in the UKIDSS DXS - Swinbank, A; Edge, A; Smail, I; Stott, J; Bremer, M; Sato, Y; Breukelen, C; Jarvis, M; Waddington, I; Clewley, L; Bergeron, J; Cotter, G; et al. (2007)
We analyse the first publicly released deep field of the UKIDSS Deep eXtragalactic Survey (DXS) to identify candidate galaxy over-densities at z~1 across ~1 sq. degree in the ELAIS-N1 field. Using I-K, J-K and K-3.6um colours we identify and spectroscopically follow-up five candidate structures with Gemini/GMOS and confirm they are all true over-densities with between five and nineteen members each. Surprisingly, all five structures lie in a narrow redshift range at z=0.89+/-0.01, although they are spread across 30Mpc on the sky. We also find a more distant over-density at z=1.09 in one of the spectroscopic survey regions. These five over-dense regions lying in a narrow redshift range indicate the presence of a supercluster in this field and by comparing with mock cluster catalogs from N-body simulations we discuss the likely properties of this structure. Overall, we show that the properties of this supercluster are similar to the well-studied Shapley and Hercules superclusters at lower redshift.